2020
DOI: 10.3390/nu12030661
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation (IL-1β) Modifies the Effect of Vitamin D and Omega-3 Long Chain Polyunsaturated Fatty Acids on Core Symptoms of Autism Spectrum Disorder—An Exploratory Pilot Study

Abstract: Background: The role of vitamin D and omega-3 long chain polyunsaturated fatty acids (omega-3 LCPUFA) in improving core symptoms of autism spectrum disorder (ASD) in children has been investigated by a few randomised controlled trials and the results are mixed and inconclusive. The response to treatment with these nutrients is heterogenous and may be influenced by inflammatory state. As an exploratory analysis, we investigated whether inflammatory state would modulate the effect of these nutrients on core symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 72 publications
0
22
0
1
Order By: Relevance
“…In addition, five original studies (reported in seven manuscripts), in which the relation between vitamin D and ASD symptoms was investigated, were found [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ] (see Table 7 ). In two larger scale RCTs, significant effects of vitamin D supplementation on respectively irritability and hyperactivity [ 76 , 77 , 78 ] and on stereotypical behavior were found [ 79 ]. In one cohort and one case control study, no significant associations were found between vitamin D supplementation at 2.5 years of age and ASD diagnosis at a mean age of 5.1 years [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, five original studies (reported in seven manuscripts), in which the relation between vitamin D and ASD symptoms was investigated, were found [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ] (see Table 7 ). In two larger scale RCTs, significant effects of vitamin D supplementation on respectively irritability and hyperactivity [ 76 , 77 , 78 ] and on stereotypical behavior were found [ 79 ]. In one cohort and one case control study, no significant associations were found between vitamin D supplementation at 2.5 years of age and ASD diagnosis at a mean age of 5.1 years [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings reported a small but not significant benefit of omega-3 PUFA supplementation in children with ASD [ 54 ]. Another 6-month RCT of omega-3 fatty acid supplements (1.5 g) vs. placebo in children 2–5 years of age with ASD does not support high-dose supplementation of omega-3 fatty acids in young children with ASD [ 55 ].…”
Section: The Role Of Omega-3 Pufa Supplementation In Asd Symptomsmentioning
confidence: 99%
“…However, limited support was given for the efficacy of omega-3 PUFA in reactive aggression and a short-term reduction in overall antisocial behavior [ 58 ]. No significant differences between groups in autism composite scores, adaptive function or language [ 55 ], and non-significantly greater improvement in hyperactivity [ 51 ] and in core symptoms of ASD [ 53 ] were found. No significant change was found in the score of the social interaction subscale by Doaei et al [ 61 ].…”
Section: The Role Of Omega-3 Pufa Supplementation In Asd Symptomsmentioning
confidence: 99%
“…The benefit obtained with n-3 LC-PUFA supplementation in ASD children is considered to be through its role in modulating inflammation ( 27 ). Some studies relate symptom severity, plasma cytokine levels, and FA profiles in ASD children ( 28 ). However, few studies correlate FA supplementation, cytokine profile, and pre- and post-intervention clinical assessment with FA.…”
Section: Introductionmentioning
confidence: 99%